Advancement in nanobubble technology: enhancing drug and nutraceutical delivery with focus on bioavailability, targeted therapy, safety, and sustainability - Awlqadr, Farhang Hameed; Noreen, Sobia; Altemimi, Ammar B.; Mohammed, Othman Abdulrahman; Qadir, Syamand Ahmed; Ahmed, Dyari H.; Alkanan, Zina T.; Tsakali, Efstathia; Van Impe, Jan F. M.; Kozak, Dmytro; Abd El-Maksoud, Ahmed A.; Ashraf, Muhammad Azeem; et al. (Frontiers in Nanotechnology, 2025)
This comprehensive review explores nanobubbles (NBs) technology advancements for improving drug and nutraceutical delivery and promoting human health. NBs are gas-filled nanocarriers owing to unique structures, excellent stability, flexibility, biocompatibility, and precise targeting abilities that stand out as promising drug delivery systems that improve bioavailability and enable controlled drug release. NBs demonstrate various applications, such as cancer therapy and cardiovascular health treatment, addressing neurodegenerative disorders, and aiding nutrient absorption. A significant advantage of NBs is their ultrasound-triggered cavitation, which enables targeted delivery with minimal systemic toxicity. In nutraceuticals, NBs enhance the absorption of vital nutrients, primarily those with poor bioavailability, by stabilizing and effectively targeting these compounds in the gastrointestinal system. However, long-term safety issues demand thorough preclinical studies, including bioaccumulation and cytotoxicity. The review examines important ethical, safety, and regulatory factors which must be addressed to advance NB technology in clinical and nutritional applications. The potential of these systems exists, but scalability and sustainability pose significant challenges. The full potential of nanocarriers in healthcare and nutrition depends on ongoing research into biodegradable materials and scalable production alongside the development of eco-friendly nanocarrier systems. Research results show NBs are fundamental to precision medicine and personalized nutrition, establishing a base for innovative drug and nutraceutical delivery systems.